A sustainable model to improve maternal health and promote early obstetric care in resource‐poor regions1. Issue 3 (15th April 2019) - Foo, Sharon; Tagore, Shephali; Mathur, Manisha; Poun, Keorany; Sam, Maly; Tan, Kok Hian; Jacobsen, Anette; Kwek, Kenneth
Abstract: Objective: To design and examine the feasibility of a sustainable training program to build local capacity and improve obstetric outcomes in Kampong Chhnang, Cambodia. Methods: A "train‐the‐trainers" model was used to conduct an obstetrics course between 2012 and 2015, its aim to reduce maternal mortality and morbidity. All Cambodian healthcare providers trained by the program were included in the study. The obstetric outcomes of all patients under the care of the trained healthcare providers were analyzed retrospectively to assess the feasibility of the program. Data from all three hospitals and 42 health centers in the province that the trainees worked at were collected from case logs. Results: There was a significant increased trend in recognition of cases of postpartum hemorrhage and pre‐eclampsia, and occurrence of difficult deliveries and cesarean deliveries ( P <0.001). The maternal mortality ratio decreased from 64.7 per 100 000 deliveries in 2012 to 40.8 per 100 000 deliveries in 2016. Conclusion: This sustainable model has the potential to positively impact obstetric education and maternal outcomes and could be adopted in other resource‐poor countries, particularly in Southeast Asia. Abstract : This sustainable model had a positive impact on obstetric education and maternal outcomes and could be adopted in other resource‐poor countries, particularly in Southeast Asia.